Oxyselenocyclization of 2‐Allylphenols for the Synthesis of 2, 3‐Dihydrobenzofuran Selenides. Issue 48 (22nd December 2021) - Hellwig, Paola S.; Barcellos, Angelita M.; Furst, Carolina G.; Alberto, Eduardo E.; Perin, Gelson
Abstract: The reaction between Oxone® and various di(hetero)aryl or alkyl diselenides enables the formation of an electrophilic selenium species in situ capable to induce the oxyselenocyclization of 2‐allylphenols. This versatile and safe protocol was explored to combine two privileged scaffolds into the structure of products: the 2, 3‐dihydrobenzofuran core and an organoselenium moiety. Fifteen 2‐[(organoselanyl)methyl]‐2, 3‐dihydrobenzofurans were produced, broadening considerably the number of known examples of this hybrid compound. Moreover, preparation of sulfur and tellurium 2, 3‐dihydrobenzofurans derivatives was also successfully demonstrated. Abstract : A convenient method is reported for the synthesis of news functionalized 2, 3‐dihydrobenzofuran selenides through the oxyselenocyclization of 2‐allylphenols in the presence of the system di(hetero)aryl or alkyl diselenides/Oxone®. This versatile and safe protocol provided fifteen 2‐[(organoselanyl)methyl]‐2, 3‐dihydrobenzofurans in good yields. The generality of the processes was also demonstrated by the preparation of sulfur and tellurium 2, 3‐dihydrobenzofurans analogues.